Suśrutasaṃhitā: "Suśrutavimarśinī"-Hindīvyākhyayā vimarśādibhiśca samanvit - Suśruta.; Śarmā, Anantarāma. (Suśruta saṃhitā of Maharṣi Suśruta, 2001)
Classical treatise, with Suśrutavimarśinī commentary on Ayurveda system in Indic medicine.
Includes indexes.
1. Sūtra-Nidānasthānātmakaḥ -- 2. Śārīra-Cikitsā-Kalpasthānātmakaḥ -- 3. Uttaratantrātmakaḥ.
Classical treatise, with Suśrutavimarśinī commentary on Ayurveda system in Indic medicine.
In Sanskrit; commentary in Hindi.
Keywords: Medicine, Ayurvedic / Early works to 1800 / http://id.loc.gov/authorities/subjects/sh2008107533